Comprehensive Updates on Antitubercular Endeavors Identified in 2023 - Sharma, Anu; Vadodariya, Palak K.; Vaddoriya, Vaidehi N.; Dhameliya, Tejas M. (Synlett, 2025)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, historically ranks among the most fatal transmissible diseases in the world. The current treatment regimens are severely challenged by the growing appearance of extensively drug-resistant (XDR) and multidrug-resistant (MDR) strains of tuberculosis. This has sparked an increase in the development of novel chemical scaffolds with significant antimycobacterial activity. In continuation of our previous coverage of novel scaffolds that are effective against tuberculosis, the present account highlights the chemical motifs, including benzimidazole, benzothiazinone, chalcone, furan, indole, oxadiazole, pyrazole, pyridine, pyrimidine, pyrrole, quinoline, quinolone, thiazole, thiophene and triazole, reported in 2023, along with an emphasis on their antitubercular (anti-TB) modes of action, minimum inhibitory concentrations from nanomolar to micromolar, promising action against MDR-TB strains, structure–activity relationships, etc. This comprehensive study provides a critical examination of recently reported anti-TB agents with a focus on their potential to address the growing challenges of drug-resistance. 1 Background2 Newly Reported Antitubercular Agents2.1 Benzimidazole2.2 Benzothiazinone2.3 Chalcone2.4 Coumarin2.5 Furan2.6 Indole2.7 Oxadiazole2.8 Pyrazole2.9 Pyridine2.10 Pyrimidine2.11 Pyrrole2.12 Quinoline2.13 Quinolone2.14 Thiazole2.15 Thiophene2.16 Triazole2.17 Miscellaneous Heterocycles3 Concluding Remarks4 Abbreviations
Keywords: tuberculosis; antitubercular agents; novel chemical scaffolds; structure–activity relationship; antimycobacterial activity